Pengaruh Pendidikan Kesehatan Menggunakan Media Video Terhadap Kecemasan Pada Pasien Pre Operasi Di Ruang Pandawa RSU Diponegoro Dua Satu Klaten - Eni Mulyani; Anik Suwarni; Atik Aryani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Surgery is an invasive procedure that involves opening body tissues. Preoperative anxiety is an unpleasant feeling that can induce fear. One non-pharmacological therapy for reducing preoperative anxiety is the provision of health education. To determine the effect of health education using video media on anxiety levels in preoperative patients in the Pandawa Ward at Diponegoro 21 Klaten General Hospital. This study employed a pre-experimental design, specifically a onegroup pretest-posttest design. The sample consisted of 52 respondents selected via purposive sampling. Data collection utilized an anxiety measurement tool based on the Amsterdam Preoperative Anxiety and Information Scale (APAIS) questionnaire. Data were analyzed using the Wilcoxon test. The study results showed a pretest median value (min-max) of 17.50 (10–22) and a posttest median value (min-max) of 12.00 (6–18). Bivariate analysis yielded a p-value of 0.001 (p<0.05); thus, it can be concluded that health education using video media affects patients experiencing preoperative anxiety. Health education using video media affects patients experiencing preoperative anxiety.